2015
DOI: 10.1016/s0924-9338(15)31320-1
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight and Obstetric Complications Determine Age at Onset in First Episode of Psychosis

Abstract: Introduction. Genetic and environmental factors involving familial antecedents and prenatal development have been described to increase risk of schizophrenia and to bring forward age at onset. Objectives. To evaluate the relationship between age at onset of psychosis (AOP) and parents age and antecedents, OCs and weight and gestational age at birth in patients with a first episode of psychosis. Method. 90 patients with first-episode psychosis were included. Socio-demographic characteristics, clinical variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Another important consideration, as per neurodevelopmental theories of the disorder (7-9), relates to potential effects of other risk factors for schizophrenia and their interactions between schizophrenia liability and cortical structure. Several obstetric complications (OCs), for example, have been consistently identified as risk factors for schizophrenia (56)(57)(58)(59)(60)(61)(62)(63) with some, such as birth weight, considered to be influenced by both genetic and environmental components (64). Previous studies have also suggested that OCs are associated with greater cortical structure deficits in schizophrenia patients compared to controls (27,63).…”
Section: Introductionmentioning
confidence: 99%
“…Another important consideration, as per neurodevelopmental theories of the disorder (7-9), relates to potential effects of other risk factors for schizophrenia and their interactions between schizophrenia liability and cortical structure. Several obstetric complications (OCs), for example, have been consistently identified as risk factors for schizophrenia (56)(57)(58)(59)(60)(61)(62)(63) with some, such as birth weight, considered to be influenced by both genetic and environmental components (64). Previous studies have also suggested that OCs are associated with greater cortical structure deficits in schizophrenia patients compared to controls (27,63).…”
Section: Introductionmentioning
confidence: 99%
“…The use of forceps and birth weight are variables that best predict AOP in the first episode of psychosis (FEP). Stimulants, which were most commonly used together with marijuana and cocaine, were the only substances associated with the earlier AOP [90].…”
Section: Low Birth Weightmentioning
confidence: 99%
“…Przy czym używanie kleszczy i masa urodzeniowa są zmiennymi, które najlepiej przewidują AOP w pierwszym epizodzie psychozy (first episode of psychosis -FEP). Leki pobudzające, które były najczęściej stosowane razem z marihuaną i kokainą, były jedynymi substancjami związanymi z wcześniejszym AOP [90]…”
Section: Powikłania Dotyczące Nieprawidłowego Wzrostu Wewnątrzpłodowegounclassified
“…Epidemiological studies have demonstrated the association of certain environmentally mediated risks with psychosis. These risk factors include urbanicity (Richardson, Hameed, Perez, Jones, & Kirkbride, ), cannabis use (Schoeler et al, ; Setién‐Suero et al, ), immigration (Kirkbride et al, ), obstetric or perinatal complications (Rubio‐Abadal et al, ), psychosocial stress (Dimitrakopoulos et al, ), childhood adversities or abuse and others (Bifulco, Bernazzani, Moran, & Jacobs, ; Stilo et al, ; Trotta et al, ). However, there is great variability in individuals regarding the reverberations of environmental exposures, hence in the field of psychosis biopsychosocial interaction seems to work in a complex way (European Network of National Networks studying Gene‐Environment Interactions in Schizophrenia, ; Van Os, Rutten, & Poulton, ).…”
Section: Introductionmentioning
confidence: 99%